Dinamika Kinerja Kedutaan Besar Republik Indonesia Di Moscow Dalam Membuka Penerbangan Langsung Jakarta - Moscow - Usmar Salam (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract This article describes the dynamics of the performance of the Indonesian embassy in Moscow in opening direct flights Jakarta - Moscow. The effort to open a Moscow-Jakarta flight is actually just a matter of time because the flight schedule has been opened and widely promoted. For the initial flight, many Indonesian people have become the first passengers of the flight which will start in early August 2017, but this flight was canceled due to a change in CEO Garuda. . This study uses secondary data collected from literature studies, interviews with informants, internet sites, institutional issues, journals, articles from newspapers and magazines, working papers, and speeches and presentations. From the results of the study it was found that in addition to the internal problems that became the main obstacle for Garuda Indonesia, there was an important note going forward that in 2020 the Indonesian Ambassador to Russia would change to a new face, whose successors had yet to be ascertained. tourism actors in Indonesia are very hopeful that whoever replaces Ambassador Wahid Supriyadi, the work to open direct flights from Jakarta to Moscow continues to be continued given that Russia is a potential tourism market.